Acid-promoted iron-catalysed dehydrogenative [4 + 2] cycloaddition for the synthesis of quinolines under air. Issue 55 (10th September 2018) - Yang, Jinfei; Meng, Xiao; Lu, Kai; Lu, Zhihao; Huang, Minliang; Wang, Chengniu; Sun, Fei
Abstract : An acid-promoted iron-catalysed dehydrogenative [4 + 2] cycloaddition reaction was developed for the synthesis of quinolines using air as a terminal oxidant. Various quinoline derivatives were obtained, and no other byproducts besides water. Abstract : An acid-promoted iron-catalysed dehydrogenative [4 + 2] cycloaddition reaction was developed for the synthesis of quinolines using air as a terminal oxidant. Acetic acid was the best cocatalyst for the cycloaddition of N -alkyl anilines with alkenes or alkynes under air. Various quinoline derivatives were obtained in satisfactory-to-excellent yields, and no other byproducts besides water were produced in the reaction. The zebrafish model has become an important vertebrate model for evaluating drug effects. We tested the activity of3n in zebrafish. The test results showed that 1 μg mL −1 3n treatments resulted in morphological malformation, and 0.01–0.1 μg mL −1 3n treatments led to potent angiogenic defects in zebrafish embryos. The results of this study will be of great significance for promoting drug research in cardiovascular and cerebrovascular diseases.